AN UNEXPECTED NEW TAXON OF SALSOLA (CHENOPODIACEAE) FROM TURKEY - FREITAG, H.; DUMAN, H. (Edinburgh Journal of Botany, 2003)
Salsola cyrenaica subsp. antalyensis (Chenopodiaceae) from the S Anatolian coast near Finike is illustrated and described as a new subspecies. Its anatomy, relationships, ecology and phytogeography are discussed. The new subspecies differs from subsp. cyrenaica by the reduced number of flowers per leaf axil, very dense axillary hairs, the smaller size of most floral organs, mostly 3 instead of 2 stigmas and 5 not 3 wings on the fruit. The new taxon grows in a narrow coastal strip of c.2km only, in open dwarf-shrub communities on limestone rocks from sea level to c.40m. It is the first representative of the S. longifolia group, sect. Coccosalsola, from Turkey and from the northern shores of the Mediterranean.